1992
DOI: 10.2343/geochemj.26.207
|View full text |Cite
|
Sign up to set email alerts
|

Uranium distribution and 234U/238U activity ratios in a sedimentary bauxite deposit, from Yangwa mine, China, and its implication for sedimentation process.

Abstract: Concentrationsof uranium and other elements in bauxite deposit from Yangwa mine at Jiaozuo area in Henan Province, China, were determined, and geochemical behavior of 234U and sedimentation process were studied by leaching experiments.An inverse correlation between two major components, A1203 and Fe203, was observed. A1203 has a distinct correlation with Ti, Cr, U and V, while Fe203 correlated with Mn, Ca and Cu. Cr, V and U were enriched in the deposit compared with crustal abundance, while Si02, MnO, MgO, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is applied to the study of soils, clay minerals, sediments, etc., and con tains various methodologies depending on the subjects and objectives. We have applied this technique to the sediments and elucidated the sedimentary environments by using some trace elements (for example, Kanai, 1986aKanai, , 1992Kanai, , 1994Kanai et al, 1990a). Although this technique provides important information about the phase and existing elements, only a few studies con cerning uranium ore deposit are reported, for ex ample, by Lowson et al (1986) and Yanase et al (1991).…”
Section: Introductionmentioning
confidence: 99%
“…It is applied to the study of soils, clay minerals, sediments, etc., and con tains various methodologies depending on the subjects and objectives. We have applied this technique to the sediments and elucidated the sedimentary environments by using some trace elements (for example, Kanai, 1986aKanai, , 1992Kanai, , 1994Kanai et al, 1990a). Although this technique provides important information about the phase and existing elements, only a few studies con cerning uranium ore deposit are reported, for ex ample, by Lowson et al (1986) and Yanase et al (1991).…”
Section: Introductionmentioning
confidence: 99%